Autophagy Competes for a Common Phosphatidylethanolamine Pool with Major Cellular PE-Consuming Pathways in Saccharomyces cerevisiae. Issue 2 (17th December 2014) - Wilson-Zbinden, Caroline; dos Santos, Aline Xavier da Silveira; Stoffel-Studer, Ingrid; van der Vaart, Aniek; Hofmann, Kay; Reggiori, Fulvio; Riezman, Howard; Kraft, Claudine; Peter, Matthias
Abstract: Autophagy is a highly regulated pathway that selectively degrades cellular constituents such as protein aggregates and excessive or damaged organelles. This transport route is characterized by engulfment of the targeted cargo by autophagosomes. The formation of these double-membrane vesicles requires the covalent conjugation of the ubiquitin-like protein Atg8 to phosphatidylethanolamine (PE). However, the origin of PE and the regulation of lipid flux required for autophagy remain poorly understood. Using a genetic screen, we found that the temperature-sensitive growth and intracellular membrane organization defects of mcd4 -174 and mcd4 -P301L mutants are suppressed by deletion of essential autophagy genes such as ATG1 or ATG7 . MCD4 encodes an ethanolamine phosphate transferase that uses PE as a precursor for an essential step in the synthesis of the glycosylphosphatidylinositol (GPI) anchor used to link a subset of plasma membrane proteins to lipid bilayers. Similar to the deletion of CHO2, a gene encoding the enzyme converting PE to phosphatidylcholine (PC), deletion of ATG7 was able to restore lipidation and plasma membrane localization of the GPI-anchored protein Gas1 and normal organization of intracellular membranes. Conversely, overexpression of Cho2 was lethal in mcd4 -174 cells grown at restrictive temperature. Quantitative lipid analysis revealed that PE levels are substantially reduced in the mcd4 -174 mutant but can be restored by deletion of ATG7 or CHO2 . Taken together, these data suggest that autophagy competes for a common PE pool with major cellular PE-consuming pathways such as the GPI anchor and PC synthesis, highlighting the possible interplay between these pathways and the existence of signals that may coordinate PE flux.